Reward and Punishment Practices for Developing Disciplinary and Religious Character at Thursina International Islamic Boarding School - Setyobudi, Nanang; Hakim, Dian Mohammad; Afifulloh, Mohammad (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
Islamic boarding schools (pesantren) are crucial in cultivating youth’s character, especially by imparting virtues such as discipline and religiosity. Thursina International Islamic Boarding School (IIBS) Malang implements a systematic approach of rewards and penalties to foster these characteristics in pupils. This study examines the conception, implementation, and assessment of the reward-and-punishment system at Thursina IIBS in cultivating students’ disciplinary and religious character. Employing a descriptive qualitative methodology with a case study framework, data were collected through interviews, observations, and documentation. Research indicates that the institution utilises a merit-demerit point system developed in collaboration with the educational and character development departments. The system is embedded in daily activities, supported by digital platforms and tangible resources, including banners, Smart TVs, and visual cues. Consistent character assessment through musyawarah with asatidz and the Tazkiyatun Nafs initiatives further augments student growth. The study finds that the system promotes consistent and sustainable character development through a balanced integration of technical, spiritual, and educational experiences.